Revolution in the revolution? : armed struggle and political struggle in Latin America - Debray, Régis (Penguin Books, 1967)
Preface to the Verso edition -- Foreword -- Introduction to the Spanish edition -- Preface -- To free the present from the past : armed self-defence ; armed propaganda ; the gue[r]rilla base ; the party and the guerrilla -- The principal lesson for the present -- Some consequences for the future.